Gene-Specific Sex Effects on Susceptibility to Infectious Diseases - Lipoldová, Marie; Demant, Peter (Frontiers in Immunology, 2021)
Inflammation is an integral part of defense against most infectious diseases. These pathogen-induced immune responses are in very many instances strongly influenced by host’s sex. As a consequence, sexual dimorphisms were observed in susceptibility to many infectious diseases. They are pathogen dose-dependent, and their outcomes depend on pathogen and even on its species or subspecies. Sex may differentially affect pathology of various organs and its influence is modified by interaction of host’s hormonal status and genotype: sex chromosomes X and Y, as well as autosomal genes. In this Mini Review we summarize the major influences of sex in human infections and subsequently focus on 22 autosomal genes/loci that modify in a sex-dependent way the response to infectious diseases in mouse models. These genes have been observed to influence susceptibility to viruses, bacteria, parasites, fungi and worms. Some sex-dependent genes/loci affect susceptibility only in females or only in males, affect both sexes, but have stronger effect in one sex; still other genes were shown to affect the disease in both sexes, but with opposite direction of effect in females and males. The understanding of mechanisms of sex-dependent differences in the course of infectious diseases may be relevant for their personalized management.